Envisioning a Different Journey: Negotiating Academe with a Chronically Ill Child - Isgro, Kirsten (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
To combine the roles of mother, scholar, and professor means walking a precarious tight rope between our own hopes and expectations and larger constraints and options. These roles carry heavy social weight—with iconic images and high expectations of what is deemed suitable and satisfactory. The personal narrative that follows chronicles the author’s ten year journey of navigating these roles amid the daily reality of caring for a child with a degenerative life-threatening illness. The essay discusses examples of best practices that higher education faculty and administrators may execute to create a culture of care in academe.